Membangun Karakter Bangsa Melalui Pendidikan Pancasila Universitas PGRI Adi Buana Surabaya - Arjuna Raffi Pradipta; Mochamad Bahrul Ulum; Naufal Nur Alfian; Mohammad Bayhaqie Febby Habibulloh; Nanda Prima Setyawan; Yoga Chandra Prianto; Rizqi Eka Firdyansyah; Muhammad Aji Pamungkas; Muhammad Nauval Rizky Alifian; Robby Suga; Jea Nur Fitriana; Suyono Suyono (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
Pancasila education in Indonesia is claimed to be the main foundation for the formation of national character. This education aims to teach basic values which include diversity, justice, unity, democracy and humanity, which are the foundation for the characteristics and morality of the Indonesian nation.This article reviews the importance of Pancasila education in forming national character values. Students are taught to respect differences of opinion, respect human rights, and practice democratic principles in everyday life. This all aims to create citizens who are fair, just and have a democratic culture. Apart from that, Pancasila education also develops a sense of love for the country and humanism. Through this education, students are taught to appreciate Indonesia's cultural and natural riches, and have the enlightenment to contribute to preserving the environment and overcoming social problems among the people.This, Pancasila education is not only about theoretical knowledge, but also about the practice of values in everyday life.